The assessment of student numeracy ability for sustainable learning in Indonesia: A study in a high school science class - Serly Anggraini Listianingrum; Edi Istiyono; Rizki Zakwandi; Muhammad Minan Chusni (Universitas PGRI Kanjuruhan Malang, 2023)
This study aimed to measure student numeracy ability within the context of physics on the kinetic theory of gases. This study employed a quantitative method with descriptive and parametric statistics analysis. Sixty-two sample students were measured for numeracy ability. The research instrument applied was the ten numeration questions that had been tested empirically. The research indicates that the student cognitive level positively influences numeracy ability with an effect size value of 0.682 and an Adj. R2 value of 0.676. Furthermore, gender-related analysis proves that there is no gap in the numeracy ability with an effect size value of 0.030 and Adj. R2 is 0.014. This study has implications for designing physics learning that develops numeracy ability, especially in determining learning designs that accommodate cognition level and gender.